2016
DOI: 10.3945/ajcn.115.113357
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein, amino acids, and vitamin D supplementation with physical activity increases fat-free mass and strength, functionality, and quality of life and decreases inflammation in sarcopenic elderly

Abstract: Supplementation with whey protein, essential amino acids, and vitamin D, in conjunction with age-appropriate exercise, not only boosts fat-free mass and strength but also enhances other aspects that contribute to well-being in sarcopenic elderly. This trial was registered at clinicaltrials.gov as NCT02402608.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
342
1
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(376 citation statements)
references
References 66 publications
17
342
1
16
Order By: Relevance
“…It is not possible to isolate the results of this trial to protein/leucine alone due to the added vitamin D (43); however, the impact of vitamin D on muscle mass and function appears to be minimal (45) or is restricted to older persons with deficient levels of vitamin D (i.e., less than 30 nmol/L) (46). In addition, a separate trial using a similarly formulated protein/leucine vitamin D-enriched supplement showed similar benefits (47). A meta-analysis examining the impact of leucine-based supplements concluded that sarcopenic patients taking leucine-based supplements gained LBM, but did not show gains in either grip or leg strength (48).…”
Section: Leucinementioning
confidence: 98%
“…It is not possible to isolate the results of this trial to protein/leucine alone due to the added vitamin D (43); however, the impact of vitamin D on muscle mass and function appears to be minimal (45) or is restricted to older persons with deficient levels of vitamin D (i.e., less than 30 nmol/L) (46). In addition, a separate trial using a similarly formulated protein/leucine vitamin D-enriched supplement showed similar benefits (47). A meta-analysis examining the impact of leucine-based supplements concluded that sarcopenic patients taking leucine-based supplements gained LBM, but did not show gains in either grip or leg strength (48).…”
Section: Leucinementioning
confidence: 98%
“…and found to be associated with increased overall mortality, its role in critically ill patients is not well described. Furthermore, studies showing a relationship between sarcopenia and vitamin D deficiency suggest that use of vitamin D may improve clinical outcomes of sarcopenia treatment as well as prevention of sarcopenia [52][53][54][55]. In an observational study, Braun et al investigated the relationship between 25-hydroxyvitamin-D (25(OH)D) deficiency at critical care initiation and all-cause mortalities in 1,325 critically ill patients.…”
Section: Vitamin D Supplementationmentioning
confidence: 99%
“…However, the difference of SAC was greater than the value expected by postural change. We assume that the increase of physical activity and change of food at home can have an additional effect on SAC (14,15) as hospitalized patients do not move as much as they typically do at home, and their food was restricted to hospital supply. Thus, postural change, physical activity, and food can be a more powerful factor for SAC than proteinuria at home, even in CKD patients with high proteinuria.…”
Section: Discussionmentioning
confidence: 99%